MANAGEMENT AND FINANCIAL STATEMENTS IN THE ACTIVITIES OF AN ECONOMIC ENTITY - Shlychkov, D.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The result of the financial and economic activity of an economic entity is its reporting. In modern economic conditions, there are two types of reporting: financial and management. Financial reporting is the main form of reporting by which investors and creditors can judge the financial position of an economic entity. Russian legislation determines the list of reporting forms and indicators that must be disclosed in financial statements. It should be noted that financial reporting is a capacious concept that consists of accounting, tax and statistical reporting. The legislative regulation of financial reporting is quite extensive from the Tax Code of the Russian Federation and the Federal Law "On Accounting" to the Regulations and Federal Accounting Standards and by-laws of accounting and financial reporting. Management accounting and management reporting is a relatively new direction in the activities of an economic entity, but at the same time it has a fairly large scientific justification for its application in the practice of doing business of an economic entity. The management accounting system is now becoming broader in understanding it is not only the cost management of an economic entity, the calculation of management analysis indicators, but also the management of information flows of an economic entity as a whole. In today's rapidly developing position of an economic entity in the structure of state regulation, it is necessary to develop provisions on the implementation of information flows for effective regulation of financial and economic activities. The research in this article is devoted to the issue of applying modern methods of building a system for regulating the information of an economic entity to obtain complete and reliable financial statements, and management reporting to achieve strategic indicators.